2018
DOI: 10.1016/j.micres.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic producing endophytic Streptomyces spp. colonize above-ground plant parts and promote shoot growth in multiple healthy and pathogen-challenged cereal crops

Abstract: The Streptomyces spp. used in this work were previously isolated as diazotrophic endophytes from sorghum stems. Here, we characterized the Streptomyces spp. for their colonization ability, plant growth promotion and protection against fungal disease in three cereals. In vitro analysis by dual culture study showed inhibitory effect on the rice pathogen Magnaporthe oryzae B157 along with inhibition of the ubiquitous phytopathogen Rhizoctonia solani by the Streptomyces spp. used in this study. The active compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 57 publications
3
19
0
1
Order By: Relevance
“…Beneficial endophytic actinobacteria with potential biocontrol characteristics have been previously isolated from diverse plant species, such as tomato (Passari et al, 2016a), cereal crops (Patel et al, 2018), and legumes (Le et al, 2016;Vijayabharathi et al, 2018). Endophytic actinobacteria augment plant growth directly through nutrient solubilization, modulation of hormone levels, nitrogen fixation (Palaniyandi et al, 2013;Golinska et al, 2015;Figueiredo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Beneficial endophytic actinobacteria with potential biocontrol characteristics have been previously isolated from diverse plant species, such as tomato (Passari et al, 2016a), cereal crops (Patel et al, 2018), and legumes (Le et al, 2016;Vijayabharathi et al, 2018). Endophytic actinobacteria augment plant growth directly through nutrient solubilization, modulation of hormone levels, nitrogen fixation (Palaniyandi et al, 2013;Golinska et al, 2015;Figueiredo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, several studies have demonstrated the potential of plant growth-promoting rhizobacteria (PGPR) for improving crop performance and yield and for controlling pathogen attack [1,6,8]. Among rhizobacteria, Streptomyces have been reported as PGPR, and despite strong interest in the medical field because of their high production of secondary metabolites, few studies have examined this group as biofertilizers or biocontrol agents [12,14,[28][29][30][31][32]. The beneficial effects of these rhizobacteria have been attributed to their ability to produce several compounds including phytohormones, siderophores, antibiotics, and lytic enzymes, as well as to fix atmospheric nitrogen, solubilize phosphate, and induce systemic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism of its action needs to be further studied. The key to the stability of biocontrol bacteria lies in the successful colonization of plant surface, body and plant rhizosphere soil (Patel et al 2018 ; Syed et al 2018 ; Thokchom et al 2017 ). Due to the influence of external environmental conditions, biocontrol bacteria in competition with the soil indigenous microorganisms is not easy to hold a dominant position in the long-term survival and colonization, which greatly affects their actual disease-preventing effect.…”
Section: Discussionmentioning
confidence: 99%